It is time to abandon apneic-oxygenation testing for brain death - James Tibballs (Archives of Organ Transplantation - Peertechz Publications, 2020)
The apneic-oxygenation test is an integral part of clinical testing to determine brain death. The medical and legal criticisms of the test are presented together which make a strong argument that it should be abandoned. The requirement for hypercarbia to stimulate spontaneous respiration also causes intra-cranial hypertension and may exacerbate an existing brain injury and as such is a self-fulfilling test. Moreover in children, the onset of spontaneous respiration may commence at levels of blood carbon dioxide in excess of the minimum level used to define brain death. It is thus also unreliable. A number of legal cases in the United States have been adjudicated in favor of plaintiffs seeking to prevent performance of the test on the basis that it causes harm. Physicians have sought to perform the apneic-oxygenation test without consent of legal guardians but have failed. In lieu of the apneic-oxygenation test a brain scan using a lipophilic radionuclide is suggested. Demonstration of absent brain blood flow may be a more stringent test to determine brain death than apneic-oxygenation but is more reliable, less invasive, not harmful and not likely to reduce the rate of organ donation.